DESAIN SISTEM TERFEDERASI DENGAN PENDEKATAN MICROSERVICE ARCHITECTURE PADA KASUS STUDI SISTEM PELAPORAN PAJAK - Darmayantie, Astie (Universitas Gunadarma, 2020)
The global economy rapidly evolves from a labor-based economy to an information-based economy. In parallel to the technological advancement, societal changes have reshaped the behaviour of end-user in acting in technology. Unlike 20 years ago, users’ are very keen to have active participation with Web technologies. The number of applications being used infers to a growing number of data and information circulation, thus creating data-driven market environment. Though centralized-approach is more preferable in most cases, however, with the growing number of usage, it is prone to single point of failure. This paper present a decentralized system design using Microservice Architecture approach. The use case of the design is for financial reporting system within an organization. Web services, REST-API technology, is adopted to ensure the interoperability of each sub-systems. A design of repository of service is also proposed to help catalogue and managing available services, thus making the proposed design scalable for future development.